Compaixão e competência cultural de enfermeiros no cuidado de populações vulneráveis - Nathalya Casallas Hernandez (2022)
Introduction: Brasil has been moving toward accepting itself as a multicultural society by acknowledging the vast presence of African American, Indigenous and Mestizo populations, while dealing with high migratory rates from every continent, and the increasing homeless population nationwide. All of these populations deserve an integral approach. Through the Unified Healthcare System (S.U.S. in portuguese), access, universality and free healthcare its guaranteed for all population, without discrimination. The Emergency Care Unit (UPA) is the main entrance to the referred healthcare system for the most vulnerable population. Nevertheless, healthcare practitioners in every level, especially nurses, need to comprehend and furthermost respect cultural diversity. Cultural competence is the capacity to provide cultural adequate and congruent care, easily accepted by the population. Aim: Understanding the process of construction of cultural competent compassion by nurses in main care of vulnerable population at the Emergency Care Unit (UPA) in Belo Horizonte, Brasil. Methods: Study conducted by qualitative approach, single case type, anchored in the theoretical framework of the Model for the Development of Culturally Competent Compassion by nurse Irena Papadopoulos. This study was carried out in an Emergency Care Unit (UPA), located in the city of Belo Horizonte (MG), Brazil. Eighteen nurses who worked at the UPA participated. Data was collected through individual online interviews guided by a semi-structured script and observation of the professional practice, from October 2020 to January 2021. The data were subjected to thematic content analysis, proposed by Bardin, with the help of ATLAS.ti software, version 9. The research was approved by the UFMG Research Ethics Committee, under the number 4,249,999. Results: Data analysis shows that the development of culturally competent compassion is a subjective, continuous and non-linear process. In addition, it enables the construction of three categories: “Building culturally competent compassion in nurses who care for vulnerable populations” is the first category. we opted for presenting three subcategories a) a look inside themselves: the recognition of cultural identity; b) Paths to be followed: from the gap to cultural knowledge; and c) Attentive listening as essential nursing care, cultural and compassionate competence as an endless opportunity for growth. The second category, "Cultural and compassionate competence of nursing during the COVID-19 pandemic in the Emergency Care Unit", is composed of three subcategories: a) Personal and professional deconstruction process; b) Strengthening professional ties based on compassion; and, c) Holistic care strategy for patients with COVID-19 and their families. Finally, “Approaches to the challenges of nursing to preserve Compassionate and Culturally Competent Care””, composed of three subcategories: a) Consolidation of compassionate skills in a globalized world; b) Culturally competent professional training as an incessant process; and c) Some ethical dilemmas in early-life compassionate care.